The influence of impact speed on chest injury outcome in whole body frontal sled impacts - Xiao, Sen; Mo, Fuhao; Yang, Jikuang; Huang, Jing; Xiao, Zhi; Crandall, Jeff R. (Transport, 2020)
While the seatbelt restraint has significantly improved occupant safety, the protection efficiency still needs further enhance to reduce the consequence of the crash. Influence of seatbelt restraint loading on chest injury under 40 km/h has been tested and documented. However, a comprehensive profiling of the efficiency of restraint systems with various impact speeds has not yet been sufficiently reported. The purpose of this study is to analyse the effect of the seatbelt loadings on chest injuries at different impact speeds utilizing a high bio-fidelity human body Finite Element (FE) model. Based on the whole-body frontal sled test configuration, the current simulation is setup using a substitute of Post-Mortem Human Subjects (PMHS). Chest injury outcomes from simulations are analysed in terms of design variables, such as seatbelt position parameters and collision speed in a full factorial experimental design. These outcomes are specifically referred to strain-based injury probabilities and four-point chest deflections caused by the change of the parameters. The results indicate that impact speed does influence chest injury outcome. The ribcage injury risk for more than 3 fractured ribs will increase from around 40 to nearly 100% when the impact speed change from 20 to 40 km/h if the seatbelt positioned at the middle-sternum of this study. Great injuries to the chest are mainly caused by the change of inertia, which indicates that chest injuries are greatly affected by the impact speed. Furthermore, the rib fracture risk and chest deflection are nonlinearly correlated with the change of the seatbelt position parameters. The study approach can serve as a reference for seatbelt virtual design. Meanwhile, it also provides basis for the research of chest injury mechanism.First published online 26 January 2021